The role of medical equipment in the spread of nosocomial infections: a cross-sectional study in four tertiary public health facilities in Uganda - Ssekitoleko, Robert T.; Oshabaheebwa, Solomon; Tusabe, Martha S.; Mugaga, Julius; Joloba, Moses L. (BMC Public Health, 2020)
With many medical equipment in hospitals coming in direct contact with healthcare workers, patients, technicians, cleaners and sometimes care givers, it is important to pay close attention to their capacity in harboring potentially harmful pathogens. The goal of this study was to assess the role that medical equipment may potentially play in hospital acquired infections in four public health facilities in Uganda. A cross-sectional study was conducted from December 2017 to January 2018 in four public health facilities in Uganda. Each piece of equipment from the neonatal department, imaging department or operating theatre were swabbed at three distinct points: a location in contact with the patient, a location in contact with the user, and a remote location unlikely to be contacted by either the patient or the user. The swabs were analyzed for bacterial growth using standard microbiological methods. Seventeen bacterial isolates were randomly selected and tested for susceptibility/resistance to common antibiotics. The data collected analyzed in STATA version 14. A total of 192 locations on 65 equipment were swabbed, with 60.4% of these locations testing positive (116/192). Nearly nine of ten equipment (57/65) tested positive for contamination in at least one location, and two out of three equipment (67.7%) tested positive in two or more locations. Of the 116 contaminated locations 52.6% were positive for Bacillus Species, 14.7% were positive for coagulase negative staphylococcus, 12.9% (15/116) were positive for E. coli, while all other bacterial species had a pooled prevalence of 19.8%. Interestingly, 55% of the remote locations were contaminated compared to 66% of the user contacted locations and 60% of the patient contacted locations. Further, 5/17 samples were resistant to at least three of the classes of antibiotics tested including penicillin, glycylcycline, tetracycline, trimethoprim sulfamethoxazole and urinary anti-infectives. These results provides strong support for strengthening overall disinfection/sterilization practices around medical equipment use in public health facilities in Uganda. There’s also need for further research to make a direct link to the bacterial isolates identified and cases of infections recorded among patients in similar settings.